Emotional Intelligence, Age and Physical Activity: Review of Contemporary Literature - Grigoriou, Στεφανία; Zisi, Βασιλική; Tachias, Φρίξος; Gilyana, Μάριλυν; Bougiesi, Μαρία (Inquiries in Physical Education and Sport, 2012)
Emotional Intelligence (EI) is considered as a person's ability to manage effectively his feelings. It is also reported as a particularly important ability for interpersonal and social relations. A strong research interest is directed not only to the concept of emotional intelligence in the workplace but also to the factors affecting it. The present research literature review studied the relationship of EI with physical activity at different age. The literature findings suggest a higher emotional intelligence of older people which means that EI is a developing process over time, possible to be learnt through life experiences. It’s seems that EI is positively related with good health and exercise habits. Most specifically participation in vigorous and moderate physical activities seems to have a positive effect on EI. The above findings connect EI and health behaviours raising the research interest of the relation between EI, exercise and physical activity at all ages.